The Effect of Using Fennel Seeds (Foeniculum vulgare L.) on Productive Performance of Broiler Chickens - Mohammed, Abdullah A.; Abbas, Rabia J. (International Journal of Poultry Science, 2009)
An experiment was conducted at the College of Agriculture Poultry Farm, University of Basra from 20/11/2007 to 2/1/2008 to study the effect of adding fennel seeds to the diet on productive performance of broiler chickens. A total of 120 day - old chicks were randomly distributed into four dietary treatments of fennel 0, 1, 2 and 3 g/kg diet contained 36% and 32% chick peas in the starter and finisher diets respectively. Results indicated that there was a significant improvement (p